P29 The role of HPV in cervical lymph node metastases from squamous cell carcinoma. Issue 5 (May 2015) - Schroeder, L.; Holzinger, D.; Baboci, L.; Pawlita, M.; Herold-Mende, C.; Heß, J.; Boscolo-Rizzo, P.; Romeo, S.; Alemany, L.; Castellsagué, X.; Quer, M.; León, X.; et al.
Abstract : Introduction: Human papillomavirus (HPV) infection is a risk factor for various cancer types, including head and neck squamous cell carcinoma (HNSCC). HPV-positive HNSCC show better survival compared to HPV-negative HNSCC despite their frequent early metastatic spread to cervical lymph nodes. Patients initially presenting only with a cervical lymph node metastasis (CLNM) during work-up are frequently diagnosed with HNSCC. In a few CLNM cases no primary tumor is detected. Aggressive multimodal treatment of these cancers of unknown primary site (CUP) often leads to substantial side effects and loss of quality of life. Recent studies provide evidence that the HPV status may have a prognostic value in CUP and may serve as a predictor for oropharyngeal localization of the primary tumor. Material and methods: In a multinational retrospective study (Heidelberg, Barcelona, Treviso) we want to determine the prevalence of HPV-driven SCC in CLNM with unknown or identified primary tumor. Presence of 51 mucosal HPV types will be analyzed in fresh-frozen and/or formalin-fixed paraffin-embedded tissue from lymph node metastases and, if available, the corresponding primary tumor. To identify truly HPV-driven cases additional markers including viral load, E6*I oncogene mRNA and expression levels of the cellular proteins p16INK4a, p53 and pRb will be determined. In addition, if fresh-frozen tissue and serum are available viral transformation-associated RNA patterns and anti-HPV antibodies, respectively, will be analyzed. Results: Results of ongoing HPV status analyses will be presented. Conclusion: These data will be correlated with clinical parameters to assess, whether active HPV involvement is associated with a better prognosis and may help to direct the search for the primary tumor towards the oropharynx. Furthermore, we want to study pairs of HPV-driven oropharyngeal tumors and the corresponding cervical lymph node metastases by comparing the HPV status and integration patterns. The study is open for participation of additional clinical collaborators.